The Development and Testing of Automatic Crutches for Disable Person - KAMARUDDIN, NURUL MAISARAH; ROSDI, M.; SAIDI, N. A. K. (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2023)
Walking aids such as canes, crutches, and walkers play a crucial role in improving a patient's base support, balance, and independence. However, conventional crutches with manual height adjustment mechanisms pose challenges for users, especially on uneven surfaces, leading to device damage and incorrect height settings. To overcome this issue, this paper introduces a crutch design that incorporates an automatic height-adjustment feature tailored to the patient's individual height. It utilises a linear actuator for height adjustment and soft materials for padding. To assess its functionality and effectiveness, a comprehensive evaluation is conducted, comparing the proposed automatic crutch to traditional axillary crutches. Experimental results demonstrate that the innovative device facilitates enhanced mobility on uneven surfaces, aids in climbing stairs, and offers personalised comfort for sitting or standing. Moreover, the cushion pad integrated into the design effectively reduces friction and pressure between the armpit and crutches, thereby mitigating the risk of armpit injuries. This research signifies a significant advancement in walking aid technology, addressing critical issues associated with manual adjustment and improving the user experience using crutches.